The growth influence of Escherichia coli co-cultured with other selected gram negative bacteria - Oyewole, OA; Hamidu, A; Egbewole, IO; Adewole, R; Oladoja, OE (Journal of Bio-Science, 2019)
This study examined the influence of Escherichia coli on the growth of other selected Gram negative bacteria (Klebsiella pneumoniae, Shigella dysenteriae, Salmonella typhi, Pseudomonas aeruginosa and Proteus vulgaris). Cultures of each bacterium at 0, 24, 48 and 72 hours of incubation were plated on MacConkey agar. Colonies that developed were counted while the optical densities were determined at 0, 24, 48 and 72 hours using spectrophotometry. Each bacterium was co-cultured with E. coli and their growth was determined using culturing method and spectrophotometry. The result showed an increase in growth in the cultures of each isolate co-cultured with E. coli when compared with single bacterium culture with the exception of P. aeruginosa. The result of this study revealed a positive growth influence between E. coli and K. pneumoniae, S. dysenteriae, S. typhi, and P. vulgaris, except for P. aeruginosa that showed a decrease in growth. J. bio-sci. 27: 101-108, 2019